The Molecular and Cellular Basis of Retinal Diseases - Pittler, Steven J.; Fliesler, Steven J. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
There are more than 300 genes that have been identified which carry mutations that cause various forms of retinal dysfunction and degeneration, making the study of retinal diseases a subject of high relevance. In this compendium of original and review articles, many of the diseases and pathways associated with disorders of the retina are examined using animal models, to provide the reader with a good overview of current retinal research. Within this volume, you will find research reports on many of the most prominent retinal disorders, such as diabetic retinopathy (DR), age-related macular degeneration (AMD), choroidal neovascularization (CNV), and retinitis pigmentosa (RP). We hope that the work presented here will stimulate new ideas and lead to effective treatments for retinal diseases.